Eisenzeitliche Siedlung auf dem Cvinger bei Dolenjske Toplice - Dular, Janez; Križ, Borut (Arheološki vestnik, 2004)
The article presents the Iron Age settlement complex of Cvingernear Dolenjske Toplice, which is composed of three tumuluscemeteries, a settlement, and an iron smelting area. Particularattention is paid to the investigation of the settlement, wheresix trenches were excavated between 1986 and 1991. Researchhas shown that Cvinger near Dolenjske Toplice was settled atthe end of the late Bronze Age. After this first phase, when thesettlement was fortified with an earthen bank and ditch, Cvingerwas abandoned for a lengthy period. It was resettled only in thelate Hallstatt period, when it was again fortified, this time witha stone rampart. Inhabitation of the settlement in the late IronAge has not yet been proven